Opportunity for Made in India medical devices in global markets: Role of Quality - SANKARAN, BALRAM; C R , Shiyas (PREPARE@u® | IEI Conferences, 2021)
Medical Device industry consist of a large number of small and medium enterprises that produce a wide variety of heterogeneous products known as medical devices. Medical devices play an important role in healthcare delivery and has a growing global demand. The domestic manufacturers of medical devices in India have a good opportunity to supply to the increasing demand in expanding global market with made in India medical devices. The quality of medical devices made in India will determine the success of Indian medical device manufacturers to become a global player